A porous single crystal zinc oxide semiconductor material with a self-supporting structure and its preparation method and application
By using a zinc-containing chalcogenide single crystal substrate to form porous single crystal zinc oxide materials under medium and high temperature conditions, the problem of difficulty in both porous structure and single crystal structure in the prior art is solved, and high purity and impurity-free The preparation of large-size porous single-crystal zinc oxide materials improves the catalytic performance of the material and the repetition of the device.
Patent Information
- Application Number
- CN202411367840.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The prior art is difficult to have porous single-crystal zinc oxide materials with both porous and single-crystal structures in large-scale growth, and the preparation process is complicated and impurities are prone to occur.
Using a zinc-containing chalcogenide single crystal substrate as the precursor parent crystal, a porous single crystal zinc oxide material with a self-supporting structure is formed under medium and high temperature conditions, and the introduction of the porous single crystal zinc oxide material is avoided. The steps of dopant.
The zinc oxide in the large-size single crystal form has a long-range ordered crystal lattice, which improves the catalytic performance of the material, and provides a simple and good repeatable porous single crystal zinc oxide substrate for zinc oxide-based semiconductor devices, solving the problem of The high purity and impurity-free material problems.
Smart Images

Figure CN118854453B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of semiconductor materials, and in particular relates to a porous single crystal zinc oxide semiconductor material with a self-supporting structure, and a preparation method and application thereof. Background Art
[0002] Zinc oxide is a II-IV compound wide bandgap direct bandgap semiconductor material, belonging to n-type semiconductor, with a room temperature bandgap of 3.37 eV and a free exciton binding energy of 60 meV. Generally speaking, stable zinc oxide has a hexagonal wurtzite structure and is a non-toxic, non-polluting, stable and environmentally friendly material. Due to its excellent thermal stability and non-toxic properties, zinc oxide has been widely used in coatings, electronics, photocatalysis and sensors.
[0003] Porous materials are generally regarded as solid materials with specific pores prepared to meet functional requirements. They have structural advantages such as high specific surface area, low relative density, and strong permeability. However, most porous materials are usually polycrystalline structures with internal defects such as grain boundaries between grains. Single crystal materials are macroscopic materials with periodically arranged and ordered repetitive structures composed of atoms, ions, etc. in three-dimensional space. Single crystal materials have unique characteristics due to their long-range ordered lattice arrangement and the absence of grain boundaries.
[0004] Porous single crystal materials are made by introducing a disordered pore phase into the original single crystal phase. They have the dual advantages of a long-range ordered lattice structure and a disordered connected pore structure. They have the characteristics of precise chemical composition, clear lattice structure, no grain boundaries, and a high specific surface area. They can be used in energy storage, catalysis, semiconductors and other fields.
[0005] The patent "Preparation and Application of ZnO Nanocrystals with Porous Hole Flower-like Structure" with publication number CN103046132A specifically discloses dissolving zinc salt in anhydrous methanol, adding urea and benzyl alcohol to mix in a certain molar ratio, stirring the mixture and transferring it into an autoclave, reacting under an argon environment, exhausting steam after the reaction and naturally cooling to room temperature to obtain a dry gray powder, and calcining to obtain a large amount of zinc oxide nanocrystal catalyst rich in porous hole flower-like structure. The patent "Porous Zinc Oxide Single Crystal and Device Using the Single Crystal" with publication number JP2014234330A specifically discloses that a pore is formed under a heating program after introducing a dopant, so that a porous zinc oxide single crystal material is introduced into a single crystal with zinc oxide as the main component. However, in the above scheme, when making porous single crystal materials, it is often necessary to add a variety of dopants or other reagents to perform pore-forming reactions, and the preparation process is complicated and the molding material has many impurities.
[0006] Zinc oxide has been widely studied as a semiconductor material with excellent performance. There is great anticipation for the large-scale growth of large-sized porous single-crystalline zinc oxide with both pore structure and single crystal structure and its application as optoelectronic semiconductor material or catalyst. Summary of the invention
[0007] In response to the problems of the above-mentioned prior art, especially the preparation of porous single crystal semiconductor materials, the present invention provides a novel porous single crystal zinc oxide semiconductor material with a self-supporting structure and a preparation method and application thereof, so that zinc oxide in large-size single crystal form has a long-range ordered lattice, the catalytic performance of the material is improved, and a porous single crystal zinc oxide substrate with simple preparation conditions and good repeatability is provided for zinc oxide-based semiconductor devices.
[0008] To achieve the purpose, the following technical solutions are provided:
[0009] The present invention provides a porous single crystal zinc oxide semiconductor material with a self-supporting structure, comprising a plurality of nanostructured nanostructured nanostructures having a size of 20 nm to 800 nm. The porous single crystal zinc oxide semiconductor material has a wurtzite structure of hexagonal system and a space group of P63mc. The porous single crystal zinc oxide semiconductor material is a porous single crystal zinc oxide film or a porous single crystal zinc oxide crystal. The surface of the porous single crystal zinc oxide film is at least one of the (100) crystal plane, (110) crystal plane, (002) crystal plane, (101) crystal plane, (102) crystal plane or (103) crystal plane of the porous single crystal zinc oxide. The surface of the porous single crystal zinc oxide crystal is at least one of the (100) crystal plane, (110) crystal plane, (002) crystal plane, (101) crystal plane, (102) crystal plane or (103) crystal plane of the porous single crystal zinc oxide. The method for preparing the porous single crystal zinc oxide semiconductor material with a self-supporting structure comprises the following steps:
[0010] (1) Using a zinc chalcogenide single crystal substrate as a precursor mother crystal, maintaining the system at a medium-high temperature state, and in an oxygen-containing atmosphere, the precursor mother crystal undergoes a solid-solid phase transition from an outer lattice to an inner lattice, and non-zinc atoms escape;
[0011] (2) Non-zinc atoms escape through the structural channels and are replaced by oxygen atoms. The remaining zinc atoms and oxygen atoms undergo secondary bonding and crystallize to form a porous single-crystalline zinc oxide semiconductor material with a self-supporting structure.
[0012] Preferably, the zinc-containing chalcogenide compound in step (1) is at least one of a sulfide, a selenide or a telluride.
[0013] Preferably, the oxygen-containing atmosphere conditions in step (1) are selected according to different zinc-chalcogenide-containing single crystal substrates, and the different oxygen-containing atmospheres are at least one of air or oxygen-argon, and meet the following conditions:
[0014] The flow rate of oxygen and argon is not less than 0.1 SLM and not more than 0.5 SLM;
[0015] The air flow rate is not less than 0.1 SLM and not more than 0.5 SLM;
[0016] When a zinc sulfide single crystal substrate is selected as the precursor mother crystal (zinc sulfide is a cubic sphalerite structure with a space group of F-43m), the decomposition reaction atmosphere is air or oxygen-argon;
[0017] When a zinc selenide single crystal substrate is selected as the precursor mother crystal, the decomposition reaction atmosphere is oxygen and argon;
[0018] When a zinc telluride single crystal substrate is selected as the precursor mother crystal, the decomposition reaction atmosphere is oxygen and argon;
[0019] SLM is the abbreviation of Standard Litre Per Minute, which means a flow rate of 1L / min under standard conditions.
[0020] Preferably, in step (1), the medium-high temperature state is a system temperature of 773 K to 1573 K, a system constant negative pressure of 0.5 Torr to 900 Torr, and a reaction time of 1 min to 500 h;
[0021] When different zinc chalcogenide-containing single crystal substrates are selected as precursor mother crystals, the system temperature, system constant pressure and reaction time are selected differently;
[0022] When zinc sulfide single crystal substrate is selected as the precursor mother crystal (zinc sulfide is a cubic sphalerite structure with a space group of F-43m), the system temperature is 773 K~1173 K, the system constant negative pressure is 1 Torr~700 Torr, and the reaction time is 30 min~100 h;
[0023] When the zinc selenide single crystal substrate is selected as the precursor mother crystal, the system temperature is 973 K~1573 K, the system constant negative pressure is 10 Torr~600 Torr, and the reaction time is 10 min~500 h;
[0024] When zinc telluride single crystal substrate is selected as the precursor mother crystal, the system temperature is 873 K~1373 K, the system constant negative pressure is 0.5 Torr~900 Torr, and the reaction time is 30 min~300 h.
[0025] Preferably, the porous single crystal zinc oxide film has a thickness of 10 nm to 100 μm.
[0026] Preferably, the size of the porous single-crystalline zinc oxide crystal is 0.1 cm to 20 cm, which refers to the macroscopic maximum length of the porous single-crystalline zinc oxide crystal.
[0027] The present invention also provides the application of the porous single crystal zinc oxide semiconductor material with a self-supporting structure in the field of photoelectric devices and photoelectric catalysis.
[0028] Compared with the prior art, the beneficial effects of the present invention are:
[0029] 1. The porous single-crystalline zinc oxide semiconductor material with a self-supporting structure provided by the present invention uses a zinc chalcogenide compound single crystal substrate as a precursor mother crystal, the breaking bond energy of the Zn-S bond, Zn-Se bond or Zn-Te bond is appropriate, the Zn-S bond, Zn-Se bond or Zn-Te bond is broken, and the Zn-O bond is generated, thereby meeting the purpose of growing into a porous single-crystalline zinc oxide semiconductor material. The transition metal chalcogenide compound has unique physical and chemical properties, abundant active sites, good conductivity, controllable electronic properties and relatively mild manufacturing conditions, and is a good precursor mother crystal.
[0030] 2. In the process of preparing the porous single-crystalline zinc oxide semiconductor material with a self-supporting structure, the present invention does not introduce any dopant for pore-forming reaction, thereby maintaining the high purity of the material and being free of impurities; under medium and high temperature conditions, the precursor mother crystal undergoes a solid-solid phase transition from the external lattice to the internal lattice, and is transformed from a solid-phase zinc sulfide compound mother single crystal into a porous single crystal of a zinc oxide solid phase. When the lattice is reconstructed, non-zinc atoms escape through specific channels of the single crystal lattice, while oxygen atoms are introduced into the single crystal lattice, and finally grow into a porous single crystal zinc oxide with a self-supporting structure; The porous single-crystal zinc oxide semiconductor material with a self-supporting structure in the present invention is grown by programmed temperature in a specific environment of constant temperature, constant negative pressure and constant flow rate, avoiding the extensive operation of introducing dopants to form pores and calcining the pore structure, and can more accurately control the material morphology and pore structure without introducing impurity elements. The challenge of growing centimeter-level porous single-crystal zinc oxide semiconductor materials and the technical difficulties in related material systems and growth processing are solved, and a porous single-crystal zinc oxide substrate with simple preparation conditions and good repeatability is provided for zinc oxide-based semiconductor devices.
[0031] 3. The present invention provides a porous single-crystalline zinc oxide semiconductor material with a self-supporting structure. First, the material has a self-supporting structure, does not rely on any template, has its own skeleton, and has its own strength and rigidity. As a semiconductor material, it can be used in different scenarios, and can maintain the overall shape and good stability of the material even in harsh environments; at the same time, no template reagent is introduced during the formation of the self-supporting structure of the present invention, and the material can be kept high in purity and free of impurities; secondly, the semiconductor material of the present invention introduces a pore structure inside the single crystal structure, which combines the advantages of porous materials and single crystal materials, and combines porosity and structural coherence. The porous structure combines porosity and structural consistency, and the single crystal skeleton minimizes energy loss at grain boundaries. The porous single-crystalline zinc oxide semiconductor material of the present invention has few crystal defects and no grain boundaries, which overcomes the defect that electron transport in traditional polycrystalline or granular zinc oxide materials is reduced due to grain boundaries, and has a catalytic activity higher than that of nanocrystals, which greatly improves the performance of porous single-crystalline zinc oxide semiconductor materials as devices in the field of photoelectric catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Sample M1 prepared in Example 1 # (110) SEM image of porous single-crystal zinc oxide crystal;
[0033] Figure 2 Sample M3 obtained in Example 3 # XRD pattern of (110) plane porous single-crystal ZnO crystal;
[0034] Figure 3 Sample M4 obtained in Example 4 # SEM image of (101) surface porous single crystal zinc oxide crystal;
[0035] Figure 4 Sample M5 obtained in Example 5 # XRD pattern of (101)-plane porous single-crystal ZnO crystal;
[0036] Figure 5 Sample M10 prepared in Example 8 # SEM image of (102)-surface porous single-crystal ZnO crystal;
[0037] Figure 6 Sample M10 prepared in Example 8 # XRD pattern of (102)-plane porous single-crystalline ZnO crystal. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Unless otherwise specified, the raw materials used in the following examples were purchased from commercial sources.
[0040] Unless otherwise specified, the methods used in the following examples are all conventional methods in the art.
[0041] When the precursor mother crystal is a zinc sulfide single crystal substrate (zinc sulfide is a cubic sphalerite structure with a space group of F-43m), the zinc sulfide single crystal substrate is prepared according to the method in the literature [Katsuhiko Ooshita, Tetsuo Inoue, Takashi Sekiguchi, Shin-ichiro Yanagiya, Atsushi Mori. Flux growth of ZnS singlecrystals and their characterization [J]. Journal of Crystal Growth, 2004 (267): 74-79.].
[0042] When the precursor mother crystal is a zinc selenide single crystal substrate, the zinc selenide single crystal substrate is prepared according to the method in the literature [Burr KF; Woods J. Growth of ZnSe single crystals from the vapour phase [J]. Journal of Crystal Growth, 1971 (9): 183-188.].
[0043] When the precursor mother crystal is a zinc telluride single crystal substrate, the zinc telluride single crystal substrate is prepared according to the method in the literature [Jin Min; Yang Wen-Hui; Wang Xiang-Hu; Li Rong-Bin; Xu Ya-Dong; Xu Jia-Yue. Growth and characterization of ZnTe single crystal via a novel Te flux vertical Bridgman method[J]. Rare Met., 2021(40): 858-864.].
[0044] There are many types of zinc-containing crystals. When selecting a single crystal substrate, it is necessary to consider factors that affect the performance, such as the broken bond energy and component composition of the precursor mother crystal reaction material. For example, cadmium zinc telluride (CdZnTe) crystals have many defects and uneven distribution of Zn components during the growth process, and dislocations and stacking faults will occur on the surface and inside of the crystal after annealing. These defects will destroy the crystal quality and seriously affect the crystal performance. In addition, CdZnTe crystals react with oxygen to generate corresponding compounds such as TeO2, CdTeO3, ZnTeO3 and other impurities, which are difficult to grow into zinc oxide crystals. Zinc germanium phosphide (ZnGeP2) crystals have surface composition deviations during growth. ZnGeP2 is a ternary semiconductor compound. The compound is prone to decomposition at high temperatures. When the crystal grows, these decomposition products such as ZnP2 and Ge are mixed in the crystal in the form of two-phase substances to form inclusions, which are difficult to grow into zinc oxide crystals. Other zinc-containing crystals also have many factors such as large lattice mismatch and excessive broken bond energy, which cannot meet the requirements. Therefore, the present invention selects a zinc chalcogenide-containing single crystal substrate as a precursor mother crystal.
[0045] Example 1
[0046] This embodiment provides a method for preparing a porous single-crystalline zinc oxide film or a porous single-crystalline zinc oxide crystal having a self-supporting structure using a zinc sulfide single crystal substrate (zinc sulfide is a cubic sphalerite structure with a space group of F-43m) as a precursor mother crystal, comprising the following steps:
[0047] A single crystal substrate of zinc sulfide (zinc sulfide is a cubic sphalerite structure with a space group of F-43m) with a size of 5 cm and a (220) crystal plane was used as a precursor mother crystal, placed on a high-purity alumina calcined boat, and placed in an alumina tube reactor. The system temperature in the reactor was heated to 973 K, and the system negative pressure was kept constant at 200 Torr. The reactor was kept in an air atmosphere with a flow rate of 0.1 SLM. Under this condition, the single crystal substrate of zinc sulfide (zinc sulfide is a cubic sphalerite structure with a space group of F-43m) underwent a solid-solid phase transition from the outer lattice to the inner lattice.
[0048] When preparing a porous single-crystalline zinc oxide film, the reaction time is 30 min to 20 h. In this embodiment, after reacting for 300 min, the film is cooled to room temperature, the sulfur atoms escape, and the zinc atoms and oxygen atoms form a porous single-crystalline zinc oxide film with a self-supporting structure on the surface of a zinc sulfide single crystal substrate (zinc sulfide is a cubic sphalerite structure with a space group of F-43m). The film thickness is 500 nm, which is recorded as sample 1. # The generated porous single-crystalline zinc oxide film has a porous structure, and the surface is at least one of the (110) surface, (100) surface, and (103) surface of the porous single-crystalline zinc oxide.
[0049] When preparing porous single-crystalline zinc oxide crystals, the reaction time is 10 h to 100 h. In this embodiment, after reacting for 30 h, the reaction is cooled to room temperature, and the sulfur atoms escape. The zinc atoms and oxygen atoms form porous single-crystalline zinc oxide crystals with a self-supporting structure on the surface of the zinc sulfide single crystal substrate (zinc sulfide is a cubic sphalerite structure with a space group of F-43m). The crystal size is 5 cm, which is recorded as sample M1. # ; The crystal face of the generated porous single-crystalline zinc oxide crystal is at least one of the (110) face, (100) face, and (103) face of the porous single-crystalline zinc oxide.
[0050] like Figure 1 As shown, this is sample M1 # The SEM image of the (110) crystal plane porous single crystal zinc oxide crystal shows the porous structure of the porous single crystal zinc oxide material. The pore size is in the range of 20 nm to 600 nm. Sample 1 # SEM images of sample M1 # similar.
[0051] Example 2
[0052] The steps of preparing a porous single-crystalline zinc oxide thin film or a porous single-crystalline zinc oxide crystal having a self-supporting structure using a zinc sulfide single crystal substrate (zinc sulfide is a cubic sphalerite structure with a space group of F-43m) as a precursor mother crystal are the same as those in Example 1, and the crystal plane of the zinc sulfide single crystal substrate (zinc sulfide is a cubic sphalerite structure with a space group of F-43m) in contact with the air atmosphere and the reaction conditions are changed to obtain different samples, namely, Sample 2 # and sample M2 # ; The correspondence between the sample number and the substrate and the reaction conditions is shown in Table 1, where, in addition to the (220) crystal plane and (111) crystal plane zinc sulfide single crystal substrate (zinc sulfide is a cubic sphalerite structure with a space group of F-43m), the (311) crystal plane zinc sulfide single crystal substrate (zinc sulfide is a cubic sphalerite structure with a space group of F-43m) can also be selected:
[0053] Table 1
[0054]
[0055] Select the conditions in Table 1 above to obtain sample 2 # The thickness of porous single crystal zinc oxide film is 50 nm~100 μm, sample M2 # The size of porous single-crystal ZnO crystals is 0.5 cm~10 cm, sample 2 # and sample M2 # Morphology and sample 1 # 、M1 # similar.
[0056] Example 3
[0057] The steps of preparing a porous single crystal zinc oxide thin film or porous single crystal zinc oxide crystal with a self-supporting structure using a zinc sulfide single crystal substrate (zinc sulfide is a cubic sphalerite structure with a space group of F-43m) as a precursor mother crystal are the same as those in Example 1. The reaction conditions are changed to obtain different samples, namely, Sample 3. # and sample M3 # ; The corresponding relationship between sample number, substrate and reaction conditions is shown in Table 2:
[0058] Table 2
[0059]
[0060] Select the conditions in Table 2 above to obtain sample 3 # The thickness of porous single crystal zinc oxide film is 50 nm~100 μm, sample M3 # The size of porous single crystal ZnO crystals is 0.5 cm~10 cm, sample 3 # and sample M3 # Morphology and sample 1 # 、M1 # Similarly, X-ray crystal diffraction and electron beam etching combined with transmission electron microscopy were used to analyze sample M3. # The atomic structure was characterized and the results are as follows Figure 2 As shown, according to the XRD pattern, a strong diffraction peak is shown at 56.71°, corresponding to the (110) plane of porous single-crystalline zinc oxide.
[0061] Example 4
[0062] This embodiment provides a method for preparing a porous single-crystal zinc oxide film or a porous single-crystal zinc oxide crystal having a self-supporting structure using a zinc selenide single crystal substrate as a precursor mother crystal, comprising the following steps:
[0063] A zinc selenide single crystal substrate with a size of 5 cm and a (110) crystal plane was used as a precursor mother crystal, placed on a high-purity alumina sinter boat, and placed in an alumina tube reactor. The system temperature in the reactor was heated to 1173 K, and the system negative pressure was kept constant at 300 Torr. The reactor was kept in an oxygen-argon atmosphere (the atmosphere consisted of argon and 5% oxygen) with a flow rate of 0.2 SLM. Under this condition, the zinc selenide single crystal substrate underwent a solid-solid phase transition from the outer lattice to the inner lattice.
[0064] When preparing a porous single-crystalline zinc oxide film, the reaction time is 10 min to 15 h. In this embodiment, after reacting for 300 min, the film is cooled to room temperature, and selenium atoms escape. Zinc atoms and oxygen atoms form a porous single-crystalline zinc oxide film sample with a self-supporting structure on the surface of the zinc selenide single crystal substrate. The film thickness is 700 nm, which is recorded as sample 4. # The generated porous single-crystalline zinc oxide film has a porous structure, and the surface is at least one of the (100) crystal plane, (002) crystal plane, and (101) crystal plane of the porous single-crystalline zinc oxide.
[0065] When preparing porous single-crystalline zinc oxide crystals, the reaction time is 10 h to 500 h. In this embodiment, after reacting for 50 h, the sample is cooled to room temperature, and selenium atoms escape. Zinc atoms and oxygen atoms form porous single-crystalline zinc oxide crystals with a self-supporting structure on the surface of the zinc selenide single crystal substrate. The crystal size is 5 cm, which is recorded as sample M4. # The surface of the generated porous single-crystal zinc oxide crystal is at least one of the (100) crystal plane, (002) crystal plane, and (101) crystal plane of the porous single-crystal zinc oxide; Figure 3 The sample shown is M4 # The SEM image of the (101) crystal plane porous single crystal zinc oxide crystal shows the porous structure of the porous single crystal zinc oxide semiconductor material. The pore size is in the range of 20 nm to 800 nm. Sample 4 # SEM images of sample M4 # similar.
[0066] Example 5
[0067] The difference between Example 5 and Example 4 is that:
[0068] A zinc selenide single crystal substrate with a size of 5 cm and a (111) crystal plane was used as the precursor mother crystal;
[0069] The system was heated to 1223 K and the system was kept at a constant negative pressure of 200 Torr. After reacting for 500 min, the system was cooled to room temperature to obtain a porous single crystal zinc oxide film sample with a thickness of 800 nm, which was recorded as sample 5. # .
[0070] The system was heated to 1223 K and the system was kept at a constant negative pressure of 200 Torr. After reacting for 100 h, the system was cooled to room temperature to obtain a porous single crystal zinc oxide sample with a crystal size of 5 cm, which was recorded as sample M5. # .
[0071] like Figure 4 The sample shown is M5 #The XRD pattern of the (101) crystal plane of the porous single-crystalline zinc oxide crystal shows that there is a diffraction peak at 36.70°, corresponding to the (101) crystal plane of the porous single-crystalline zinc oxide crystal.
[0072] In addition to the substrates of the above-mentioned embodiments 4 and 5, a (100) crystal plane zinc selenide single crystal substrate may also be selected.
[0073] Example 6
[0074] The steps of preparing a porous single crystal zinc oxide thin film with a self-supporting structure using a zinc selenide single crystal substrate as a precursor mother crystal are the same as those in Example 4. The reaction conditions are changed to obtain different samples, namely, Sample 6. # ~Sample 9 # ; The corresponding relationship between sample number, substrate and reaction conditions is shown in Table 3:
[0075] Table 3
[0076]
[0077] Select the conditions in Table 3 above to obtain the porous single crystal zinc oxide film sample 6 # ~Sample 9 # The thickness is in the range of 100nm~70 μm.
[0078] Example 7
[0079] The steps of preparing a porous single crystal zinc oxide crystal with a self-supporting structure using a zinc selenide single crystal substrate as a precursor mother crystal are the same as those in Example 4. The reaction conditions are changed to obtain a different sample, namely, sample M6. # ~Sample M9 # ; The corresponding relationship between sample number, substrate and reaction conditions is shown in Table 3:
[0080] Table 4
[0081]
[0082] The porous single crystal zinc oxide sample M6 was imaged using a scanning electron microscope. # ~Sample M9 # The morphology of sample M6 was characterized. # ~Sample M9 # All have pores ranging from 20 nm to 800 nm; sample M6 # ~Sample M9 # The morphology of sample M4 # Similar, it has a porous skeleton structure.
[0083] Example 8
[0084] This embodiment provides a method for preparing a porous single-crystal zinc oxide thin film or a porous single-crystal zinc oxide crystal having a self-supporting structure using a zinc telluride single crystal substrate as a precursor mother crystal, comprising the following steps:
[0085] A zinc telluride single crystal substrate with a size of 15 cm and a (111) crystal plane was used as a precursor mother crystal, placed on a high-purity alumina sinter boat, and placed in an alumina tube reactor. The system temperature in the reactor was heated to 923 K, and the system negative pressure was kept constant at 500 Torr. The reactor was kept in an oxygen-argon atmosphere (the atmosphere consisted of argon and 5% oxygen) with a flow rate of 0.2 SLM. Under this condition, the zinc telluride single crystal substrate underwent a solid-solid phase transition from the outer lattice to the inner lattice.
[0086] When preparing a porous single-crystalline zinc oxide film, the reaction time is 30 min to 30 h. In this embodiment, after reacting for 350 min, the film is cooled to room temperature, and the tellurium atoms escape. The zinc atoms and oxygen atoms form a porous single-crystalline zinc oxide film sample with a self-supporting structure on the surface of the zinc telluride single crystal substrate. The film thickness is 300 nm, which is recorded as sample 10. # The generated porous single-crystalline zinc oxide film has a porous structure, and the surface is at least one of the (110) crystal plane, (002) crystal plane, and (102) crystal plane of the porous single-crystalline zinc oxide.
[0087] When preparing porous single-crystalline zinc oxide crystals, the reaction time is 5 h to 300 h. In this embodiment, after reacting for 80 h, the sample is cooled to room temperature, and the tellurium atoms escape. The zinc atoms and oxygen atoms can generate porous single-crystalline zinc oxide crystals with a self-supporting structure on the surface of the zinc telluride single crystal substrate. The crystal size is 15 cm, which is recorded as sample M10. # The surface of the generated porous single-crystalline zinc oxide crystal is at least one of the (110) crystal plane, (002) crystal plane, and (102) crystal plane of the porous single-crystalline zinc oxide.
[0088] like Figure 5 The sample shown is M10 # SEM image of porous single-crystal ZnO crystal with (102) crystal plane, sample 10 # SEM image of sample M10 # Similarly, it can be seen from the figure that it has a porous skeleton structure and the pore sizes are all in the range of 50 nm to 800 nm.
[0089] like Figure 6 As shown, X-ray crystal diffraction and electron beam etching combined with transmission electron microscopy were used to analyze sample 10. # 、Sample M10 # The atomic structure characterization was carried out, and the XRD spectrum showed a diffraction peak at 48.09°, corresponding to the (102) crystal plane of the porous single-crystalline ZnO crystal.
[0090] Example 9
[0091] The steps of preparing a porous single crystal zinc oxide thin film with a self-supporting structure using a zinc telluride single crystal substrate as a precursor mother crystal are the same as those in Example 8. The crystal plane of the zinc telluride single crystal substrate in contact with the oxygen-argon atmosphere and the reaction conditions are changed to obtain different samples, namely, Sample 11. # ~Sample 14 # ; The corresponding relationship between sample number, substrate and reaction conditions is shown in Table 5;
[0092] Table 5
[0093]
[0094] Select the conditions in Table 5 to obtain the porous single crystal zinc oxide film sample 11 # ~Sample 14 # The thickness is in the range of 300 nm~100 μm.
[0095] Example 10
[0096] The steps of preparing a porous single-crystal zinc oxide crystal with a self-supporting structure using a zinc telluride single crystal substrate as a precursor mother crystal are the same as those in Example 8. Different samples are obtained by changing the substrate and reaction conditions, namely, sample M11. # ~Sample M14 # ; The corresponding relationship between sample number, substrate and reaction conditions is shown in Table 6:
[0097] Table 6
[0098]
[0099] Scanning electron microscopy was used to examine sample M11. # ~Sample M14 # The morphology of sample M11 was characterized. # ~Sample M14 # All have pores ranging from 50 nm to 800 nm, which is similar to sample M10. # The morphology is similar and has a porous structure.
[0100] Sample M11 # ~Sample M14 # The scanning electron microscope images of sample M11 # ~Sample M14 # Similarly, the pore size of the products is in the range of 50 nm to 800 nm.
[0101] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A porous single crystal zinc oxide semiconductor material with a self-supporting structure, characterized in that: The porous single crystal zinc oxide semiconductor material has a size of 20 nm to 800 nm and is a worm-like three-dimensional disordered interconnected pore; the porous single crystal zinc oxide semiconductor material is a hexagonal wurtzite structure with a space group of P63mc; the porous single crystal zinc oxide semiconductor material is a porous single crystal zinc oxide film or a porous single crystal zinc oxide crystal; the surface of the porous single crystal zinc oxide film is at least one of the (100) crystal plane, (110) crystal plane, (002) crystal plane, (101) crystal plane, (102) crystal plane or (103) crystal plane of the porous single crystal zinc oxide; the surface of the porous single crystal zinc oxide crystal is at least one of the (100) crystal plane, (110) crystal plane, (002) crystal plane, (101) crystal plane, (102) crystal plane or (103) crystal plane of the porous single crystal zinc oxide; the preparation method of the porous single crystal zinc oxide semiconductor material with a self-supporting structure comprises the following steps: (1) Using a zinc chalcogenide single crystal substrate as a precursor mother crystal, maintaining the system at a medium-high temperature state, and in an oxygen-containing atmosphere, the precursor mother crystal undergoes a solid-solid phase transition from an outer lattice to an inner lattice, and non-zinc atoms escape; (2) Non-zinc atoms escape through the structural channels and are replaced by oxygen atoms. The remaining zinc atoms and oxygen atoms undergo secondary bonding and crystallize to form a porous single-crystalline zinc oxide semiconductor material with a self-supporting structure.
2. The porous single crystal zinc oxide semiconductor material with a self-supporting structure according to claim 1, characterized in that: The zinc-containing chalcogenide compound in step (1) is at least one of a sulfide, a selenide or a telluride.
3. The porous single crystal zinc oxide semiconductor material with a self-supporting structure according to claim 1, characterized in that: The oxygen-containing atmosphere conditions in step (1) are selected according to different zinc-sulfur compound-containing single crystal substrates. The different oxygen-containing atmospheres are at least one of air or oxygen-argon and meet the following conditions: The flow rate of oxygen and argon is not less than 0.1 SLM and not more than 0.5 SLM; The air flow rate is not less than 0.1 SLM and not more than 0.5 SLM.
4. The porous single crystal zinc oxide semiconductor material with a self-supporting structure according to claim 1, characterized in that: In step (1), the medium-high temperature state is a system temperature of 773 K to 1573 K, a system constant negative pressure of 0.5 Torr to 900 Torr, and a reaction time of 1 min to 500 h.
5. The porous single crystal zinc oxide semiconductor material with a self-supporting structure according to claim 1, characterized in that: The porous single crystal zinc oxide film has a thickness of 10 nm to 100 μm.
6. The porous single crystal zinc oxide semiconductor material with a self-supporting structure according to claim 1, characterized in that: The size of the porous single-crystal zinc oxide crystal is 0.1 cm to 20 cm.
7. Application of the porous single-crystal zinc oxide semiconductor material with a self-supporting structure according to claim 1 in the fields of optoelectronic devices and photoelectric catalysis.
Citation Information
Patent Citations
Preparation and application of ZnO nanometer monocrystal with porous flower-like structure
CN103046132A
Porous zinc oxide single crystal, and device using single crystal
JP2014234330A
Porous oxide single crystal material as well as preparation method and application thereof
CN117966269A